Primary pulmonary nuclear protein of the testis midline carcinoma: case report and systematic review with pooled analysis - Zhao, Dong; Cao, Wei; Zha, Shiqian; Wang, Yixuan; Pan, Zhou; Zhang, Jingyi; Hu, Ke (Frontiers in Oncology, 2024)
Nuclear protein of the testis (NUT) midline carcinoma (NMC) is a rare tumor, with particularly low incidence in the lungs, and a correspondingly poor prognosis. To determine the clinicopathological characteristics, outcomes, and prognostic factors of primary pulmonary NMC, a case was reported and a systematic review was performed. Twenty-nine records, including ours, involving 62 cases, were finally included. The median age at diagnosis was 29.5 years. At presentation, the most common symptoms at presentation were cough (47.50%) and chest/back pain (37.50%). In terms of diagnosis, 32.14% of NMC cases were identified through immunohistochemistry (IHC); However, a greater number of cases may be misdiagnosed initially, and ultimately, the diagnosis of NMC was confirmed through a combination of IHC and fluorescence in situ hybridization (FISH). Despite the clinical application of various chemotherapy-based treatments, the actual effectiveness remains unsatisfactory. Furthermore, Cox regression analysis of multiple factors identified male gender and concurrent presence of pleural effusion as indicators of shorter survival time in patients. These results emphasize the importance of increased diagnostic awareness among clinical and pathology practitioners concerning NMC. While there is currently no established standard for treating NMC, a treatment approach combining multiple methods shows promise for future research. Concurrently, clinical and foundational investigations addressing variables such as gender and the presence of pleural effusion may yield valuable insights into the diagnosis and treatment of NMC.